2015
DOI: 10.1210/jc.2014-3896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Factors Associated With Area and Metabolic Activity in the Visceral and Subcutaneous Adipose Tissues by FDG-PET/CT

Abstract: The present study demonstrated that area and metabolic activity in VAT and SAT could be differently regulated, suggesting the involvement of AGEs and PEDF in adipose tissue inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…So far, we have found that glyceraldehyde-derived AGE levels are (a) correlated with a soluble form of RAGE that could reflect tissue RAGE expression in both nondiabetic and diabetic subjects (104)(105)(106)(107), thus suggesting a marker of the activation of AGE-RAGE axis; (b) associated with low-density lipoprotein cholesterol levels and thrombogenic markers such as plasminogen activator inhibitor-1 and fibrinogen in a general population (108)(109)(110); (c) elevated under oxidative stress, chronic kidney disease and/or diabetic conditions and corre-lated with inflammatory biomarkers such as monocyte chemoattractant protein-1, the soluble form of vascular cell adhesion molecule-1 and ADMA (106,107,(111)(112)(113); (d) increased in nonalcoholic steatohepatitis (NASH) patients and associated with insulin resistance in both NASH subjects and an non-NASH general population (114)(115)(116); (e) correlated with serum PEDF and DPP-4 levels, markers of insulin resistance (117,118); (f) associated with visceral and subcutaneous adipose tissue inflammation and decreased adiponectin levels (114,119); (g) correlated with vascular inflammation and endothelial dysfunction in high-risk patients (120,121); (h) inversely associated with number and migratory activity of EPCs (122), thus suggesting the involvement of this type of AGEs in impaired endothelial cell repair; and (i) significantly associated with plaque progression in patients with acute coronary syndrome (123). Moreover, atrovastatin, pioglitazone and α-glucosidase inhibitor have been shown to significantly decrease serum levels of glyceraldehyde-derived AGEs, which are associated with reduced biomarker levels for organ damage in diabetic, chronic kidney disease or NASH subjects (120,(124)(125)(126)(127)(128).…”
Section: Measuring Serum Levels Of Ages and Its Clinical Utilitymentioning
confidence: 99%
“…So far, we have found that glyceraldehyde-derived AGE levels are (a) correlated with a soluble form of RAGE that could reflect tissue RAGE expression in both nondiabetic and diabetic subjects (104)(105)(106)(107), thus suggesting a marker of the activation of AGE-RAGE axis; (b) associated with low-density lipoprotein cholesterol levels and thrombogenic markers such as plasminogen activator inhibitor-1 and fibrinogen in a general population (108)(109)(110); (c) elevated under oxidative stress, chronic kidney disease and/or diabetic conditions and corre-lated with inflammatory biomarkers such as monocyte chemoattractant protein-1, the soluble form of vascular cell adhesion molecule-1 and ADMA (106,107,(111)(112)(113); (d) increased in nonalcoholic steatohepatitis (NASH) patients and associated with insulin resistance in both NASH subjects and an non-NASH general population (114)(115)(116); (e) correlated with serum PEDF and DPP-4 levels, markers of insulin resistance (117,118); (f) associated with visceral and subcutaneous adipose tissue inflammation and decreased adiponectin levels (114,119); (g) correlated with vascular inflammation and endothelial dysfunction in high-risk patients (120,121); (h) inversely associated with number and migratory activity of EPCs (122), thus suggesting the involvement of this type of AGEs in impaired endothelial cell repair; and (i) significantly associated with plaque progression in patients with acute coronary syndrome (123). Moreover, atrovastatin, pioglitazone and α-glucosidase inhibitor have been shown to significantly decrease serum levels of glyceraldehyde-derived AGEs, which are associated with reduced biomarker levels for organ damage in diabetic, chronic kidney disease or NASH subjects (120,(124)(125)(126)(127)(128).…”
Section: Measuring Serum Levels Of Ages and Its Clinical Utilitymentioning
confidence: 99%
“…Recent studies have suggested that AGEs are formed not only from reducing sugars (i.e., GA, glucose, and fructose), but also from carbonyl compounds (i.e., AA, GO, and MGO) derived from the auto-oxidation of sugars and other metabolic pathways [41,42,43,44]. Evidence to show that GA- and AA-derived AGEs (GA-AGEs and AA-AGEs) play a role in the pathophysiology of various disorders, such as non-alcoholic/alcoholic liver and brain injury [45,46,47,48,49,50,51,52], cardiovascular diseases (CVD) [44,53,54,55,56,57], T2DM and diabetic vascular complications [41,42,43,44,45,58], Alzheimer’s disease (AD) [43,50,59,60,61,62], and cancer [63,64,65,66,67], is increasing. In the present study, we discussed the pathophysiological roles of GA- and AA-AGEs, predominant components of toxic AGEs (TAGE), and a related novel theory for preventing the onset/progression of NAFLD/NASH and ALD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that metabolic activity in the VAT and SAT might be differentially regulated and FDG-PET/CT imaging could be a reliable tool for evaluating this parameter and to complement the cardiometabolic risk calculation. 5,6 The aims of this study were the evaluation of the uptake of FDG by VAT and SAT and to determine differences in patients with and without obesity who underwent whole body 18 FDG-PET/CT scanning for clinical purposes (cancer diagnosis or staging).…”
Section: Introductionmentioning
confidence: 99%